The Digitalisation of Employment, Fiqh Education and Empowerment of Migrant Workers’ Rights - Nur Chanifah; Fahd bin Mohana bin Salim al-Ahmadi; Abu Samsudin; Nurul Islami; Muhammad Najih Vargholy (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study aims to analyse the digital transformation of fiqh education on labour for Indonesian migrant workers (PMI) in the United Arab Emirates from a transnational perspective, focusing on how Islamic legal literacy can be an instrument of empowerment and protection of workers' rights. This study uses a socio-legal approach that combines normative fiqh studies with the socio-legal reality in the field. Data was collected through in-depth interviews, observation, and documentation. Data analysis was carried out in stages of data reduction, data presentation, and conclusion drawing. The results of the study show that there is a significant gap between normative knowledge of fiqh labour and the reality experienced by PMI in the UAE. The transformation of digital-based fiqh education can be used as a solution to this gap, as it can expand access to legal literacy, strengthen awareness of transformative maqāṣid, and provide practical skills in negotiating rights. The digitisation of fiqh education on labour issues not only functions as a medium of education but also as a transnational advocacy strategy that strengthens the protection and empowerment of PMI in a global context. This research contributes empirically to overcoming barriers to the implementation of migrant workers' rights in the UAE and recommends a maqāṣid transformative-based digital fiqh education module and strategic policy measures to strengthen the protection of migrant workers' rights.